(untitled) (Ius Novum, 2023)
The subject of the article are the regulations concerning the escape of a person legally deprived of liberty, that are in force in countries with a Germanic legal tradition. The analysis of German, Swiss, Austrian and the Principality of Liechtenstein’s law is conducted against a background of Polish solutions. The aim of the study is to present similarities and differences between the solutions adopted in particular German-speaking countries, as well as between these solutions and the regulations contained in the Polish Penal Code.